GOING INTERNATIONAL: KTP WELL RECEIVED IN TRANSFERRING KNOWLEDGE FROM UNIVERSITY TO COMMUNITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 8 April 2015 Knowledge transfer programmes (KTP) which were first introduced in 2010 are part of the Critical Agenda Programmes (CAP) of the Ministry of Education Malaysia and will be expanded to an international platform to strengthen the role of higher education in transferring expertise to the industry and community.